Layanan Home Visit Pada Era New Normal di Sekolah Dasar - Rustariani, Erli; Tastin, Tastin; Syarifuddin, Ahmad (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The objectives of this research are: 1) Describe the planning of home visit services in the new normal era in elementary schools, 2) Describe the implementation of home visits in the new normal era in elementary schools, 3) describe the evaluation of home visit services in the new normal era in elementary schools. This research uses qualitative research methods with phenomological research type. The data collection techniques used were interviews, observation and documentation. The data analysis technique uses source, method and time triangulation techniques. The results of this research show that 1) the learning process used by West Kikim 3 Elementary School in the new normal era uses a home visit service. 2) The planning stage for home visit services in elementary schools includes planning where at this stage the teacher divides groups based on the nearest place of residence, makes a visit schedule, contacts the students' parents to inform them that the home visit service will be implemented and creates a WhatsApp group. 3) Implementation Stage, namely the teacher visits the study group home according to a predetermined schedule. 4) The evaluation stage, seen from the process, can be seen through the attitude and enthusiasm of the students and seen from the results, it can be assessed whether the home visit service has an effect on the students or not. 5) The obstacles experienced during the learning process using the home visit service were that there were several parents of students who suddenly changed the meeting schedule, limited teaching aids and vehicle access to the students' homes.